Water Resources in Kashkadarya Region and Modern Approach to Their Use - Abduhalimova Nafisa Meyli qizi (Indonesian Journal of Innovation Studies, 2022)
in this article water resources in kashkadarya region and modern approach to their use, the main rivers and their tributaries that receive water inagriculture are given. Water distribution facilities are analyzed by district and drip irrigation is highlighted when using water.